Afghanistan's Islam From Conversion to the Taliban - Green, Nile (University of California Press, 2016)
This book provides the first overview of the history and development of Islam in Afghanistan. Written by leading international experts, chapters cover every era from the conversion of Afghanistan through the medieval period to the present day. Based on primary sources in Arabic, Persian, Pashto, Uzbek, and Urdu, its depth of coverage is unrivalled in providing a developmental picture of Afghanistan's Islam, including such issues as the rise of Sufism, women's religiosity, state religious policies, and transnational Islamism. Looking beyond the unifying rhetoric of theology, the book reveals the disparate and contested forms of Afghanistan's Islam. "Islam in Afghanistan has long been viewed as static and uniform, but this fine collection demonstrates that it has been far more contested and dynamic over the centuries than either Afghans or outside observers have realized. This book opens a door to that history to reveal a religious tradition that has constantly adapted itself to changing intellectual currents, local cultural beliefs, and political upheavals." -THOMAS BARFIELD, Boston University "A pathbreaking book that challenges us to think in new and more sophisticated ways about Islam in Afghanistan, in the past as well as in the present. It is essential reading for anyone seeking to go beyond stereotyped images of a monolithic and timeless Islam in Afghanistan and in other Muslim societies." -ROBERT D. CREWS, Stanford University NILE GREEN is Professor of South Asian and Islamic History at the University of California, Los Angeles. He is the author of Sufism: A Global History and Terrains of Exchange: Religious Economies of Global Islam.